Privatizing punishment: testing theories of public support for private prison and immigration detention facilities - Enns, Peter K. (Criminology, 2018)
The transfer of authority over the supervision of inmate populations from state and federal governments to private corporations is one of the most significant contemporary developments in the criminal justice system. Yet, the controversy surrounding the private prison industry has occurred in U.S. criminal justice policy circles without any understanding of the public's preferences toward these institutions. In this article, we test several theories that potentially explain opinions toward privatizing carceral institutions: the racial animus, business is better, conflict of interest, and problem‐escalation models. These models are tested with original data from the 2014 Cooperative Congressional Election Survey. The data show that opinions toward the privatization of carceral institutions do not neatly fall along partisan or ideological divisions but are explained by beliefs about racial resentment, corporate ethics, and the potential ability of private companies to provide services cheaper than the public sphere. The results hold important implications for how we understand the future of private carceral institutions in the United States.